Hands-On : supporting hand rehabilitation movements in playtherapy videogame (2018)
The main objective of this project is to extend the scope of Playtherapy: Videojuego de apoyo a terapias de recuperación física, in order to cover the hands movement rehabilitation therapies. This project arose from the necessity of finding alternatives for conventional therapies, which usually turn out to be monotonous and boring; this factors may cause a demotivation by patients and their later desertion. Thereby, with the purpose of face this weaknesses, PlayTherapy project was created, this video game pretends to be a tool for physiotherapists, and try to make physical therapies more interesting and fun in such a way that it increases the motivations of patients.